THE INFLUENCE OF RETURN ON ASSET (ROA), PRICE EARNING RATIO (PER), AND EARNING PER SHARE (EPS) ON STOCK PRICES IN PT COMMUNICATION CABLE SYSTEM INDONESIA, TBK - Bungan, Rati; Kannapadang, Dwibin; Mantong, Agustinus (JURNAL EKBIS, 2024)
This research aims to determine the effect of ROA, PER and EPS on share prices. This type of research uses a quantitative approach. The population in this research is the Indonesian Communication Cable System company Tbk with the research sample using the balance sheet and profit and loss report of the Indonesian Communication Cable System company for the period 2021-2023. The instrument testing techniques used are multiple linear regression analysis, coefficient of determination test and hypothesis testing. The results of this research show that the Return On Asset (ROA) variable has a significant effect on stock prices, while the Price Earning Ratio (PER) variable has a positive but not significant effect on stock prices and the Earning Per Share (EPS) variable has a significant effect on stock prices. Simultaneously, the variables Return on Assets (ROA), Price Earning Ratio (PER) and Earning Per Share (EPS) together influence stock returns.